Constructive and Destructive Processes During the 2018–2019 Eruption Episode at Shiveluch Volcano, Kamchatka, Studied From Satellite and Aerial Data - Shevchenko, Alina V.; Dvigalo, Viktor N.; Zorn, Edgar U.; Vassileva, Magdalena S.; Massimetti, Francesco; Walter, Thomas R.; Svirid, Ilya Yu.; Chirkov, Sergey A.; Ozerov, Alexey Yu.; Tsvetkov, Valery A.; Borisov, Ilya A. (Frontiers in Earth Science, 2021)
Dome-building volcanoes often develop by intrusion and extrusion, recurrent destabilization and sector collapses, and renewed volcanic growth inside the collapse embayment. However, details of the structural architecture affiliated with renewed volcanic activity and the influences of regional structures remain poorly understood. Here, we analyze the recent activity of Shiveluch volcano, Kamchatka Peninsula, characterized by repeated episodes of lava dome growth and destruction due to large explosions and gravity-driven collapses. We collect and process a multisensor dataset comprising high-resolution optical (aerial and tri-stereo Pleiades satellite), radar (TerraSAR-X and TanDEM-X satellites), and thermal (aerial and MODIS, Sentinel-2, and Landsat 8 satellites) data. We investigate the evolution of the 2018-2019 eruption episode and evaluate the morphological and structural changes that led to the 29 August 2019 explosive eruption and partial dome collapse. Our results show that a new massive lava lobe gradually extruded onto the SW flank of the dome, concurrent with magmatic intrusion into the eastern dome sector, adding 0.15 km3 to the lava dome complex. As the amphitheater infilled, new eruption craters emerged along a SW-NE alignment close to the amphitheater rim. Then, the large 29 August 2019 explosive eruption occurred, followed by partial dome collapse, which was initially directed away from this SW-NE trend. The eruption and collapse removed 0.11 km3 of the dome edifice and led to the formation of a new central SW-NE-elongated crater with dimensions of 430 m × 490 m, a collapse scar at the eastern part of the dome, and pyroclastic density currents that traveled ~12 km downslope. This work sheds light on the structural architecture dominated by a SW-NE lineament and the complex interplay of volcano constructive and destructive processes. We develop a conceptual model emphasizing the relevance of structural trends, namely, (1) a SW-NE-oriented (possibly regional) structure and (2) the infilled amphitheater and decollement plane, both of which are vital for understanding the directions of growth and collapse and for assessing the potential hazards at both Shiveluch and dome-building volcanoes elsewhere.